Complex negotiations: The lived experience of enacting agency after a stroke. (January 2015) - Bergström, Aileen L.; Eriksson, Gunilla; Asaba, Eric; Erikson, Anette; Tham, Kerstin
Abstract Objective: This qualitative, longitudinal, descriptive study aimed to understand the lived experience of enacting agency, and to describe the phenomenon of agency and the meaning structure of the phenomenon during the year after a stroke. Agency is defined as making things happen in everyday life through one's actions. Methods: This study followed six persons (three men and three women, ages 63 to 89), interviewed on four separate occasions. Interview data were analysed using the Empirical Phenomenological Psychological method. Results: The main findings showed that the participants experienced enacting agency in their everyday lives after stroke as negotiating different characteristics over a span of time, a range of difficulty, and in a number of activities, making these negotiations complex. The four characteristics described how the participants made things happen in their everyday lives through managing their disrupted bodies, taking into account their past and envisioning their futures, dealing with the world outside themselves, and negotiating through internal dialogues. Conclusions: This empirical evidence regarding negotiations challenges traditional definitions of agency and a new definition of agency is proposed. Understanding clients' complex negotiations and offering innovative solutions to train in real-life situations may help in the process of enabling occupations after a stroke.